Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1042/bsr20170684
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of all-trans retinoic acid in the regulation of apelin expression in vascular endothelial cells

Abstract: The apelin gene can promote vascular endothelial cell (VEC) proliferation, migration, and angiogenesis. However, the molecular mechanism for regulation of the apelin gene is still unknown. Real-time PCR and Western blotting analysis were employed to detect the effect of all-trans retinoic acid (ATRA) in up-regulating apelin expression in human umbilical vein endothelial cells (HUVECs). Furthermore, the in vivo study also indicated that ATRA could increase apelin expression in balloon-injured arteries of rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(31 reference statements)
3
4
0
Order By: Relevance
“…Retinoids such as tretinoin are important regulators of cell division and proliferation. Its cosmetic effects on the skin are well known, and several studies have demonstrated the effects of tretinoin on blood vessels [43,44,45]. The current results suggest that BCE may exert an effect similar to that of tretinoin on HUVECs.…”
Section: Resultssupporting
confidence: 51%
“…Retinoids such as tretinoin are important regulators of cell division and proliferation. Its cosmetic effects on the skin are well known, and several studies have demonstrated the effects of tretinoin on blood vessels [43,44,45]. The current results suggest that BCE may exert an effect similar to that of tretinoin on HUVECs.…”
Section: Resultssupporting
confidence: 51%
“…The results are also in agreement with previous studies reported that injection of cisplatin is accompanied with a significant elevation of MDA content and a marked depletion in GSH content as well as SOD and CAT activities [30]. ATRA is known to have free radical scavenger effects [31], which explain the present results that found that administration of ATRA attenuated the effects of ROS through the decreasing of MDA content and increasing of GSH and CAT activities.…”
Section: A B C D E Fsupporting
confidence: 94%
“…Hypoxia increases apelin gene expression in cultured human pulmonary arterial endothelial and smooth muscle cells via hypoxia inducible factor–1α (HIF-1α) dependent mechanism (Eyries, et al, 2008). Activation of α-retinoic acid receptors by all-trans retinoic acid increases apelin gene expression in HUVEC cells and in carotid arteries from balloon-injured rats (Shi, et al, 2017). Although these studies provide insight into several key pathways involved in apelin regulation, the association between apelin gene expression and release of apelin into the circulation and/or surrounding tissues remains poorly understood.…”
Section: Apelinmentioning
confidence: 99%